Globalization and gender inequality: Evidence from South Africa - Caro Janse Van Rensburg; Carli Bezuidenhout; Marianne Matthee; Victor Stolzenburg (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Inequality has been rising in most countries for several decades, with negative consequences for social cohesion and economic growth. Substantial gender wage gaps contribute significantly to overall wage inequality. We look at an often-overlooked driver of gender inequality: international trade. Trading firms constitute 70 per cent of employment in South African manufacturing and, hence, have a large impact on the country's labour dynamics. Using employer- employee matched data on the universe of formal South African manufacturing firms, we show that these firms exhibit greater gender wage gaps than non-traders. The effect seems to be driven by trading firms requiring more flexibility from their workforce in interactions with customers and suppliers across continents and time zones. As women are-or are considered to be-less flexible because of uneven household responsibilities, they receive a lower trading wage premium than men. We find no evidence for other potential channels.
Keywords: F16; J16; J31; 330; gender wage gap; international trade; employer-employee matched data; South Africa